Предмет: Алгебра,
автор: rudelguan
помогите решить пример
Приложения:
Ответы
Автор ответа:
0
Cosx - 2 = 2Cosx/2
2Cos²x/2 -1 - 2 = 2Cosx/2
2Cos²x/2 - 2Cosx/2 -3 = 0
Cosx/2 = t
2t² -2t -3 = 0
t =(1+-√7)/2
t₁= (1+√7)/2 t₂= (1-√7)/2
Cosx/2 =(1+√7)/2 Cosx/2 = (1-√7)/2
∅ ∅
2Cos²x/2 -1 - 2 = 2Cosx/2
2Cos²x/2 - 2Cosx/2 -3 = 0
Cosx/2 = t
2t² -2t -3 = 0
t =(1+-√7)/2
t₁= (1+√7)/2 t₂= (1-√7)/2
Cosx/2 =(1+√7)/2 Cosx/2 = (1-√7)/2
∅ ∅
Похожие вопросы
Предмет: Биология,
автор: kremovichkris
Предмет: Русский язык,
автор: gnazirova3
Предмет: Русский язык,
автор: Аноним
Предмет: Физика,
автор: Grizzlies666
Предмет: Химия,
автор: абвгдежз12345678